1992
DOI: 10.1002/1097-0142(19920601)69:11<2676::aid-cncr2820691109>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Sarcomatoid carcinoma of the prostate a clinicopathologic study of 12 patients

Abstract: Sarcomatoid carcinoma of the prostate is a rare tumor that can be difficult to distinguish from a true sarcoma. The authors report 12 patients in whom the typical light microscopic appearance of prostatic adenocarcinoma was accompanied by the appearance of spindled or pleomorphic sarcomatoid areas within the same specimen or in subsequent accessions. Immunostaining or electron microscopic study demonstrated epithelial differentiation within the sarcomatoid area(s) in 6 of the 11 patients in whom special studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(34 citation statements)
references
References 22 publications
2
31
0
1
Order By: Relevance
“…[8][9][10] Tumors are most commonly composed of an admixture of both malignant glandular and spindle cell elements, in which cases with predominantly a sarcomatoid component may be mistaken for a sarcoma. In support of the term 'sarcomatoid carcinoma' it has been demonstrated that both the malignant epithelial and spindle cell components are clonally related.…”
Section: Sarcomatoid Carcinoma Of the Prostatementioning
confidence: 99%
“…[8][9][10] Tumors are most commonly composed of an admixture of both malignant glandular and spindle cell elements, in which cases with predominantly a sarcomatoid component may be mistaken for a sarcoma. In support of the term 'sarcomatoid carcinoma' it has been demonstrated that both the malignant epithelial and spindle cell components are clonally related.…”
Section: Sarcomatoid Carcinoma Of the Prostatementioning
confidence: 99%
“…15 These tumors are rare, but do occur in the prostate gland. [65][66][67][68][69][70][71][72] Clinically, these patients tend to be older and in roughly half of cases have a history of prostatic adenocarcinoma treated by radiation. 66,68 The tumors produce bladder outlet obstruction and often require repeated TURs to control local symptoms.…”
Section: Sarcomatoid Carcinomamentioning
confidence: 99%
“…66,68,73 In adults, these are almost always leiomyosarcoma and will stain appropriately. In recurrent tumors, the mesenchymal component usually overgrows the epithelial and so a pure sarcomatous pattern in the setting of pretreated adenocarcinoma should be assumed to represent sarcomatoid carcinoma.…”
Section: Sarcomatoid Carcinomamentioning
confidence: 99%
“…PPC is defined as a poorly-differentiated NSCLC with ≥10% giant and/or spindle cell components, or as a carcinoma comprised completely of giant and spindle cells in the new WHO Classification of Lung Cancers (13). PPC is believed to be more aggressive and exhibit a poorer prognosis than ordinary lung carcinomas (1,3,14). There are few studies with regard to the chemotherapy of PPC, and its clinical and pathological characteristics therefore remain unclear.…”
Section: Discussionmentioning
confidence: 99%